Developing Sustainable Tourism through Competency-Based Training for Geotourism Guides in Sadi Village: Pengembangan Pariwisata Berkelanjutan Melalui Pelatihan Pemandu Geowisata Berbasis Kompetensi di Desa Sadi - Matilda Metboki; Lidia Paskalia Nipu; Herry Zadrak Kotta; Robertho Kadji; Irene Augusta Boymau; Andreas Sinuhaji (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Sadi Village, located in East Tasifeto District, Belu Regency, East Nusa Tenggara Province, possesses significant geological and paleontological value, particularly related to the discovery of ancient elephant (Stegodon) fossils. This scientific potential provides strong prospects for development as an educational geotourism destination. However, its utilization remains limited due to the insufficient number and competencies of local geotourism guides. This community service program aims to strengthen the capacity of local guides through competency-based training to support sustainable tourism development in Sadi Village. The program was implemented through a needs assessment, preparation of competency-based training materials, offline training sessions integrating theoretical instruction and field practice, and evaluation through guiding simulations. The training covered basic geology and paleontology, geotourism interpretation techniques, guiding ethics, and communication skills. The results indicate improvements in participants’ knowledge, interpretative skills, communication abilities, and professional confidence in delivering geological information. Furthermore, the program fostered active involvement of local youth and community members in managing and promoting the geotourism site. The activity demonstrates that competency-based training can enhance local human resource quality and contribute to strengthening the geotourism identity of Sadi Village while supporting sustainable tourism development.